THE INFLUENCE OF PRICE PERCEPTION, BRAND TRUST, AND ONLINE CUSTOMER REVIEWS ON THE PURCHASE DECISION OF SKINTIFIC SKINCARE AMONG STUDENTS OF MERCU BUANA UNIVERSITY YOGYAKARTA - Fadhi, Taufik Nur; Nuvriasari, Audita; Grefanti, Risa; Saputra, Yohanes Agus Adi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the influence of price perception, brand trust, and online customer reviews on purchasing decisions of Skintific skincare products among students at Universitas Mercu Buana Yogyakarta. The research adopts a quantitative approach with a causal associative design. A total of 100 respondents were selected using purposive sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression techniques.The findings reveal that, simultaneously, price perception, brand trust, and online customer reviews significantly influence purchasing decisions. Partially, price perception and online customer reviews have a positive and significant effect on purchasing decisions, whereas brand trust does not show a significant influence. Among the independent variables, online customer reviews emerge as the most dominant factor affecting purchasing decisions.These results indicate that young consumers tend to rely more heavily on peer-generated reviews and perceived value for money rather than solely on brand trust. The study offers important implications for digital marketing strategies, emphasizing the need to strengthen competitive price positioning and actively manage online customer reviews as credible and persuasive sources of consumer information. Keywords: Price Perception; Brand Trust; Online Customer Reviews; Purchasing Decisions; Skintific